"Snare-Ride": A Bailout Technique to Catheterize Target Vessels With Unfriendly Anatomy in Branched Endovascular Aortic Repair. (August 2017) - Ferreira, Marcelo; Katsargyris, Athanasios; Rodrigues, Eduardo; Ferreira, Diego; Cunha, Rodrigo; Bicalho, Guilherme; Oderich, Gustavo; Verhoeven, Eric L. G.
Purpose: To describe a novel endovascular bailout technique for successful completion of target vessel stenting during branched stent-graft repair of thoracoabdominal aortic aneurysms (TAAA) after encountering difficulties with standard catheterization techniques.Technique: Technical difficulties when using fenestrated and branched grafts should be expected, especially in difficult anatomy or when an off-the-shelf device (eg, standard 4-branch device) is used that does not perfectly "match" the anatomy. The "snare-ride technique" facilitates antegrade transaxillary side branch catheterization and stent placement during TAAA branched grafting using a snare via a transfemoral approach. The branch of the graft is catheterized from an axillary access. The respective target vessel is then catheterized via a femoral access. An Indy snare is advanced over the transfemoral wire and positioned near the entrance of the target vessel. The transaxillary wire inside the branch of the graft is then advanced, snared, and pushed inside the target vessel with the snare. The procedure is thereafter continued with antegrade bridging of the target vessel in routine fashion.Conclusion: The snare-ride technique can be a useful maneuver to catheterize target vessels with difficult anatomy in TAAA branched stent-graft repair. Early experience shows safety and feasibility.